Effect of post-reflow cooling rate on intermetallic compound formation between Sn–3.5 Ag solder and Ni–P under bump metallization - He, Min (2012)
Cooling rate is an important parameter in solder reflow process because it influences not only microstructure of solder alloy but also the morphology and growth of intermetallic compounds (IMC) formed between solder and its metallization. All these ultimately affect the mechanical integrity of the joint. In this work, the effect of cooling rate on IMC growth is studied in Sn–3.5 Ag solder/Ni–P under bump metallization (UBM) system. Morphology and growth kinetics of the formed Ni3Sn4 IMC under different cooling rates are studied. Needle-type, boomerang-type and chunk-type of Ni3Sn4 IMCs have been observed between solder and Ni–P UBM under various cooling conditions. The amount of the needle-type and boomerang-type grains decreases with the increase of reflow time. Prolonged reflow results in continuous layer of chunk-type IMC grains with no obvious effect from the cooling rate. Samples with different post-reflow cooling rate are further annealed. It is found that the IMC layer thickness increases faster in samples under fast cooling rate than the slow ones under the same annealing condition.